Painless Colonoscopy: Available Techniques and Instruments - Hyun Gun Kim (Korean Society of Gastrointestinal Endoscopy, 2016)
During colonoscopy, air insufflation to distend the lumen and facilitate careful inspection and scope insertion can induce pain and cause discomfort. Carbon dioxide (CO2) insufflation can decrease abdominal pain and discomfort during and after colonoscopy. The advantage of CO2 insufflation is the rapid absorption of the gas across the intestine. Another painless option is water-assisted colonoscopy. Two methods for water-assisted colonoscopy are available: water immersion and water exchange. In a recent direct comparison, the water exchange method was superior to water immersion, CO2 insufflation, and air insufflation with respect to pain during colonoscopy, although it still had the disadvantage of being a time-consuming procedure. Cap-assisted colonoscopy is a simple technique involving the use of a small transparent cap attached to the tip of the scope. Three studies showed an advantage of this technique in terms of reduced patient discomfort compared with the conventional method. Three robotic colonoscopy systems (Endotics System [Era Endoscopy], NeoGuide [NeoGuide Systems Inc.], and Invendoscope [Invendo Medical]) have been introduced to evaluate pain reduction during colonoscopy, but none has been widely adopted and used in practice. In this review, clinical trials of several techniques and new devices for painless colonoscopy are described and summarized.